Design of Fashion Products with Pawestri Batik Motifs from Lamongan - Shobrina Fairuzzahra; Nova Kristiana (Universitas Negeri Surabaya, 2025)
Batik is a cultural heritage of Indonesia that needs preservation, yet it is currently less favored by younger generations due to outdated perceptions and lack of modern relevance. This design project aims to develop Lamongan’s batik motifs into modern interpretations that appeal to youth. A qualitative method was employed, including observation, interviews, and literature studies of Pawestri Batik. The result was four primary motifs including milkfish, catfish, jasmine, and crab that transformed into vibrant batik fabrics. These were applied to various fashion products and supported by a catalog as promotional media. The conclusion indicates that modern visual integration without losing traditional values can increase youth interest in local batik.